Comparison of Different Parameters in the Diagnosis of Acute Abdomen - Ahmet Kocakuşlak; Hülya Özdemir Leylek; Mustafa An›l Yaşar (Haseki Tıp Bülteni, 2011)
Aim: Acute abdominal syndrome (AAS) defines the failure to establish the primary diagnosis rather than being a definitive diagnosis. The fact that many patients are discharged from the hospital without surgical intervention as well as the decision regarding which patients should undergo surgery and when, all may create a dilemma for the clinician. Methods: We analyzed and recorded the data of 50 randomly chosen patients with a primary diagnosis of AAS who had been hospitalized in the emergency surgical department for follow-up. The study group was compared with a control group (50 patients) who had been directly operated on for AAS without a preceding observation. The parameters used in the study were age, gender, guarding, rebound tenderness, ultrasonography, leucocytosis, and left shift of the neutrophils. Results: The mean age of the patients in the study group was statistically significantly higher than that in the control group and surgery was not necessary in 88%.Statistically significant difference was found between the two groups for guarding, rebound tenderness, ultrasonography, and gender. Logistic regression analysis revealed that rebound tenderness and ultrasonography results were more valuable than the other parameters. Rebound tenderness and ultrasonography influenced the decision for surgical intervention by 7.9- and 17.3- fold increases, respectively. Conclusion: We think that our parameters can be used as a guide by clinicians working in emergency departments to decide which patient should be operated on since only 12% of the study group had necessitated surgical intervention. (The Medical Bulletin of Haseki 2011;49: 77-83